Teachers’ Perception and Effectiveness of the use of Edu-Driven Apps in Lagos State During Covid-19 Pandemic Era - Olujuwon, Olutola; Okuntade, Japhet; Udofia, Imoh; Akinkuotu, Foluke; Ismail, Muideen (Ilorin Journal of Education, 2022)
The event of Covid-19 caused unusual opportunities for teachers who are technologically naive in the use of technological devices. This pandemic prompted the Lagos State Government to build an Edu-driven App to mitigate the impact of face-to-face classroom engagement, which was disrupted during the Covid-19 pandemic. The Lagos State government’s educational reaction to the Covid-19 outbreak was investigated in this study. The study also explored how teachers perceived Edu-driven Apps as stakeholders in the teaching profession by providing a quick overview of some common Apps utilized by teachers. The descriptive research design was used. The target population consisted all in-service teachers from public secondary schools in the six educational districts across the state respectively. Two hundred and forty respondents were selected by purposive sampling by the researchers. A 20-item researcher-designed questionnaire with a 4- point Likert type response scale was used to generate data. The descriptive and Chi-square statistical analysis were used to analyze the data at a .05 significance level. The findings showed that the use of Edu-driven Apps during covid-19 pandemic was beneficial to students in Lagos State and that the perception of the teachers on the use of Edu-driven Apps also assisted the teachers in teaching effectively. The study recommended the continuous training of the end-users of the Edu-driven Apps and the development of local content.